Determination of public transport organization indicators and assessment of their importance - Samuilovas, Andrius; Ušpalytė-Vitkūnienė, Rasa (International Conference “Environmental Engineering”, 2026)
Public transport plays a vital role in urban mobility, ensuring accessibility, sustainability and the economic development of cities and regions. To achieve these goals, it is important to systematically monitor and evaluate performance, ideally using real-time, daily data. Performance indicators are quantitative and qualitative measures used to assess different aspects of a public transport system, including reliability, safety, environmental impact, fleet management and operational efficiency (for example, in the selection process of operators). However, not all of these indicators are equally important and must be assessed comprehensively. Determining the relative importance of each indicator helps organizations to focus on the aspects that best meet their policy objectives and customer expectations. This paper synthesizes current research to outline key service indicators and explores the disparities in public transport delivery across diverse urban landscapes.
Keywords: accessibility; indicators; quantitative measures; qualitative measures; public transport (PT); reliability; urban mobility